Corporate acquisitions and bank relationships - Vadym Volosovych; Steven Poelhekke; Razvan Vlahu (Tinbergen Institute, 2021)
Using a large dataset of firm-bank and ownership information for 23 European countries over 2008-2015, we study the dynamics of bank relationships after corporate acquisitions and the effects of changing banks on firm performance. Foreign acquirers do not rely on internal capital markets but keep targets' domestic banks. With more domestic banks, firms increase fixed capital and trade credit. In contrast, domestic acquirers remove domestic but add foreign banks. The latter mainly help reduce the cost of financing. We further explore firm and bank heterogeneity and confirm cost of financing and information asymmetry as plausible reasons to change banks.
Keywords: D82; E51; F36; G21; G34; 330; Acquisitions; Firm-bank relationships; Firm financing; Operating performance